2005
DOI: 10.1021/ie049276w
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Study of the Adsorption of Aromatic Hydrocarbons (Benzene, Toluene, and p-Xylene) on Dealuminated Clinoptilolites

Abstract: Adsorption of benzene, toluene, and p-xylene (BTX) on dealuminated clinoptilolites was investigated in the temperature range of 398-498 K by way of the inverse gas chromatography method. The dealuminated zeolites were prepared via a chosen number of acid treatments of natural clinoptilolite precursors with aqueous HCl. Both natural and acid-leached substrates were characterized by X-ray diffraction, N 2 adsorption at 76 K, and BTX adsorption. The Freundlich, Langmuir, and Dubinin-Astakhov adsorption models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 27 publications
(40 reference statements)
0
36
0
1
Order By: Relevance
“…Esta curvatura también puede ser relacionada al fenómeno de multicapas de adsorción que se esta realizando en los mesoporos y área externa de la zeolita. En esta isoterma de alta resolución se observan los distintos mecanismos de adsorción que ocurren en la adsorción de N 2 a 76 K. [18]. En los gráficos  s se consideró el intervalo comprendido entre 0.05 a 2.4, figura 7a y de 0.05-0.4 para los gráficos de alta resolución, figura 7b.…”
Section: Adsorción De Nitrógenounclassified
“…Esta curvatura también puede ser relacionada al fenómeno de multicapas de adsorción que se esta realizando en los mesoporos y área externa de la zeolita. En esta isoterma de alta resolución se observan los distintos mecanismos de adsorción que ocurren en la adsorción de N 2 a 76 K. [18]. En los gráficos  s se consideró el intervalo comprendido entre 0.05 a 2.4, figura 7a y de 0.05-0.4 para los gráficos de alta resolución, figura 7b.…”
Section: Adsorción De Nitrógenounclassified
“…The zeolite was modified to enhancing the adsorption of VOCs. As described by Hernandez et al (2005), it was two times washed by 1 N HCl for 6 h at 50°C with a moderate shaking and then rinsed several times by distilled water. Finally, the zeolite grains were dried at 180°C (Hernandez et al, 2005).…”
Section: Materials and Methods Preparation Of The Bedsmentioning
confidence: 99%
“…This study has focused on comparison of the BTXs elimination and mineralization on Fe 0 , Cu 2 O and Fe 0 -Cu 2 O nanoparticles coated zeolite bed. Previous studies showed adsorption of VOCs on natural zeolites such as clinoptilolite; for instance, Hernandez et al (2005) showed the BTXs adsorption on clinoptilolite and they found that dealumination of the zeolite increases its adsorption capability for BTXs (Hernandez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The increase of temperature favors this adsorption to occur more easily given that the activation energy can be surmounted more readily. In the case of benzene (C 6 H 6 ), the smaller size of the molecule leads to easy adsorption without need of large activation energies, this reflects the fact that the kinetic diameter of C 6 H 6 molecule is smaller than those of toluene and o-xylene [17].…”
Section: Equilibrium Isothermsmentioning
confidence: 99%